Socioeconomic Effects on Psychosocial Factors Among Low-Income Older Adults. (11th March 2022) - Sargent, Lana; Zanjani, Faika; Winship, Jodi; Gendron, Tracey; Mackiewicz, Marissa; Diallo, Ana; Waters, Leland; Battle, Kimberly; Ford, Gregory; Falls, Katherine; Chung, Jane; Price, Elvin T.; et al.
Objectives: Older adults have been disproportionately affected by COVID-19. The primary goal of this study is to determine the socioeconomic effects on psychosocial factors among low-income independent-living older adults, in an urban setting, during the COVID-pandemic. Methods: Participants were recruited through Virginia Commonwealth University's Richmond Health and Wellness Program. Telephone surveys ( n =100) were conducted using the Epidemic – Pandemic Impacts Inventory Geriatric with the Racial/Ethnic Discrimination addendum. Responses were analyzed for income and education effects across seven domains: home life, social activities/isolation, economic, emotional health-wellbeing, physical health, COVID-infection history, and positive change behaviors/experiences. Results: The sample population was between 51 and 87 years of age, 88% were Black, 57% reported incomes of 10, 000/year or less, and 60% reported a high-school education or less. There were income effects for social activities/isolation (f = 3.69, p <.05) and positive change (f = 8.40, p <.01), and education effects for COVID History (f = 4.20, p <.04). Discussion: Overall results highlight the social patterns for a diverse sample of low-income urban older adults; education and income are identified as risk factors for social losses, COVID-infection experiences, racial/ethnic discrimination during the COVID-pandemic, and positive change behaviors.